Perbandingan Jumlah Donasi Darah Sebelum dan Saat Pandemi Covid-19 di UTD PMI Banyumas Tahun 2019 dan 2020 - Ahmad Fauzi; Francisca Romana Sri Supadmi; Nurpuji Mumpuni (Jurnal Surya Medika (JSM), 2021)
Blood donation is someone who voluntarily gives blood; then, the feasibility is processed and transfused to patients in need. Blood donors come from voluntary blood donors or substitute donors/families or certain communities. The COVID-19 pandemic is the spread of a coronavirus epidemic that has spread to various continents and countries. This research is a quantitative descriptive study with a time approach used as a retrospective. The number of donations before the pandemic was 18,661, the number of donations during the pandemic was 22,882, and media for disseminating information using the Whatsapp application. The increase in the number of blood donations during the COVID-19 pandemic and the efforts made to keep donors from donating blood during the COVID-19 pandemic.